Short-term effects of additional sensory information in mobility and gait speed in older fallers - Carvalho, Isabela Feitosa de; Leme, Gianluca Loyolla Montanari; Scheicher, Marcos Eduardo (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Postural balance consists of information emanating from the interaction of visual, somatosensory and vestibular systens. This information is impaired in aging, leading to postural control changes in the elderly, increasing the risk of falls in this population. The postural balance may be improved with the addition of sensory information, such as a subpatelar bandage. Objective: To investigate the effect of using additional sensory information in gait speed and functional mobility of older fallers. Methods: 28 elderly women were evaluated, all were considered fallers. The test Timed Up and Go (TUG) was used to assess functional mobility and 10m Test to evaluate the gait speed. The tests were performed with and without the addition of additional sensory information (subpatelar strip). The normality was verified by the Shapiro-Wilk test and the results were compared using paired Student t test and Wilcoxon test. Results: There was significant difference in the TUG (p = 0.0006) and in the gait speed (p = 0.004) with and without subpatelar strip. Conclusion: The use of additional sensory information increased the gait speed and functional mobility of older fallers.